(untitled) (Educação e Pesquisa, 2022)
This work aims to understand the representations made by Gildásio Amado, who was considered a cultural mediator, about the experimental secondary classes, which were the pioneering essay of pedagogical innovation in Brazilian secondary education in the 1950s and 1960s. These representations are analyzed in two texts produced by Gildásio Amado as head of the Secondary Education Board of the Ministry of Education and Culture during the implementation of the experimental secondary classes, and in two other texts, written by him, after the first cycle of this pedagogical experience. To read this question, we used the concept of representation developed by the historian Roger Chartier, which has two dimensions: the presentification of the absent or what has passed, but also, necessarily, the construction of this absent. Thus, the operation of the production of past facts and processes is carried out from the interests and ideologies of their authors. On the one hand, Gildásio Amado’s look, as a high-ranking official of the Ministry of Education and Culture, at the experimental secondary classes at the time of their enthusiastic implementation are analyzed. On the other hand, we seek to understand the author’s view also on the experimental secondary classes after the performance of their first cycle, which presents a more evaluative character. We seek, therefore, to perceive Gildásio Amado’s evaluations of the first wave of renewal of Brazilian secondary education in two different historical moments.